2019
DOI: 10.1016/j.neuro.2019.02.001
|View full text |Cite
|
Sign up to set email alerts
|

d-Amphetamine and methylmercury exposure during adolescence alters sensitivity to monoamine uptake inhibitors in adult mice

Abstract: Gestational exposure to methylmercury (MeHg), an environmental neurotoxicant, and adolescent administration of d-amphetamine (d-AMP) disrupt dopamine neurotransmission and alter voluntary behavior in adult rodents. We determined the impact of adolescent exposure to MeHg and dAMP on monoamine neurotransmission in mice by assessing sensitivity to acute dAMP , desipramine, and clomipramine, drugs that target dopamine, norepinephrine, and serotonin reuptake, respectively. Male C57Bl/6n mice were given 0 (control) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 71 publications
0
1
0
Order By: Relevance
“…In another study with male rats exposed to MeHg during adolescent development, it was shown that the effects of MeHg exposure on adult neurobehaviors including attention and memory were augmented by the dopamine agonist, d-amphetamine [ 57 ]. A follow-up study concluded that adolescence was vulnerable to MeHg and d-amphetamine, and the effect persisted in adulthood [ 58 ]. These studies provide important bases for the involvement of dopamine neurotransmission system in behavioral toxicity of MeHg, particularly in the behaviors related to ADHD [ 57 ].…”
Section: Introductionmentioning
confidence: 99%
“…In another study with male rats exposed to MeHg during adolescent development, it was shown that the effects of MeHg exposure on adult neurobehaviors including attention and memory were augmented by the dopamine agonist, d-amphetamine [ 57 ]. A follow-up study concluded that adolescence was vulnerable to MeHg and d-amphetamine, and the effect persisted in adulthood [ 58 ]. These studies provide important bases for the involvement of dopamine neurotransmission system in behavioral toxicity of MeHg, particularly in the behaviors related to ADHD [ 57 ].…”
Section: Introductionmentioning
confidence: 99%